Initiating culturally responsive teaching for identity construction in the Malaysian classrooms - Idrus, Faizah (Canadian Centre for Science and Education, 2014)
This article presents evidence to the need for Culturally Responsive Teaching (CRT) to construct students’ identity in the Malaysian classrooms. Since an important objective of education is to prepare individuals to exercise efficaciously in their environment, all students in multicultural society could benefit from exposure to CRT (Gay, 2000). In this study, a specific text (Ah Khaw Goes to Heaven) was used in the English literature classroom, which depicted conflicts in multicultural Malaya in the 1940s. A qualitative inquiry employing semi-structured, in depth interviews with 9 English language teachers in 6 schools around Kuala Lumpur were carried out. Classroom observations were conducted, and group interviews with 6 groups of students were also carried out. Thematic analysis were performed and the findings suggest that students’ interpretation of CRT were influenced by an orthodox perception of their identity in the classroom and in the teaching and learning process, while teachers were more skeptical and reserved in developing CRT.